New uses for vitamin C, and its versatile, pleiotropic antioxidant action. - Treatment of neoplasms, skin diseases, bone diseases and stimulation of the immune system - Adamus, Justyna; Abram, Kamila; Banaś, Patryk; Pierzchała, Jakub Rafał; Bednarz, Katarzyna; Sobańska, Natalia; Banasiak, Aleksandra Paulina; Teichman, Rafał; Kasprowicz, Jakub; Hyjek, Michał (Journal of Education, Health and Sport, 2023)
Introduction: Vitamin C (Vit C) is an organic chemical compound from the group of unsaturated polyhydroxy alcohols. It influences physiological processes such as the facilitation of iron absorption, hormone and carnitine synthesis, and is also involved in epigenetic processes. It is a vitamin, which means that it must be provided in food. It is also an antioxidant used as a food additive. In recent times, its pleiotropic use has been proven in the treatment of immune deficiencies, the treatment of skin diseases, bone diseases and may also be used in new cancer treatment regimens. Aim of the study: To review the current literature on the use of vitamin C in various fields of health and science. Materials and Methods: We reviewed the literature available in PubMed, using the key words: "vitamin C"; "ascorbid acid"; "cancer treatment"; "vitamin C immune function". Results: Vitamin C has pleiotropic effects on the human body, both through its effects on cells and tissues and through its antioxidant mechanisms and regulation of gene expression. It has been shown to be a key antioxidant with anti-inflammatory and immune system supportive effects. Its effect of slowing down skin photo-ageing by reducing the amount of metalloproteinases induced by reactive oxygen species has been noted in the literature. Vitamin C has been shown in studies to reduce the risk of osteoporosis due to its osteoclast inhibitory properties. Beneficial effects of high-dose intravenous infusions have also been demonstrated in the treatment of cancer, as well as about reducing organ failure and vascular damage in patients with ARDS and sepsis. Summary: The versatile action of vitamin C has made it the subject of intense research. However, the reports in the literature to date on its use require further studies on larger groups of people to confirm its effects.